Acclimatation of the roe deer (Capreolus capreolus L.) introduced in a supramediterranean habitat and its occupation of space (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
In 1988 and 1989, we captured 74 roe deer (Capreolus capreolus) in the Chize National Reserve in France and transferred them to the Monts de Vaucluse. Thirteen individuals were followed by radio-tracking during two years. The study area, a supramediterranean habitat dominated by Quercus humilis and Quercus ilex covered 40,000 ha. The instrumented deer were located daily during the three first months, the longest time required to settle on a home range, and once a week thereafter. These data allowed us to calculate survival rates and size of home ranges. The mean survival rate during the first year after the introduction was 85 %. Except for one adult male and one adult female, all radio-equipped deer established their home range within 3 km of the release site. The time required for definitive establishment on a home range varied from 45 to 85 days after release. The mean area prospected before settling on a home range was greater for adults (n = 5) than for juveniles (n = 6) (2,240 ha vs. 478 ha). Conversely, the mean home range size after the period of prospection was greater for juveniles (n = 6) than for adults (n = 4) (823 ha vs. 342 ha). If capture, transport and release are carried out under good conditions, the roe deer can adapt to the Mediterranean climate and habitat.
APS